A Critical Review of the Evidence Base of Imagery Rehearsal for Posttraumatic Nightmares: Pointing the Way for Future Research. Issue 5 (30th September 2013) - Harb, Gerlinde C.; Phelps, Andrea J.; Forbes, David; Ross, Richard J.; Gehrman, Philip R.; Cook, Joan M.
<x xml:space="preserve">Abstract</x> In this article, the authors provide information on key characteristics of imagery rehearsal treatment protocols and examine the quality of reporting of randomized controlled and uncontrolled trials of imagery rehearsal for treating posttraumatic nightmares. Using a reliable and valid scale, two independent psychologists rated 16 trials. Most reports provided insufficient information on a range of variables including the definition of treatment delivery (e.g., therapist supervision, treatment fidelity), description of the participant sample, data analysis (e.g., determination of sample size), and treatment assignment (e.g., randomization procedures). Low methodological quality and poor reporting can lead to inflation of estimates of treatment effects and inadequately substantiated conclusions, such as inflated effect sizes in meta‐analytic studies. Numerous imagery rehearsal protocols exist, but in some cases are given different names and tested in pilot studies, slowing progression in the field. Randomized controlled trials of imagery rehearsal with credible comparison conditions, examination of predictors of dropout and outcome, as well as dismantling studies of imagery rehearsal treatment components are needed.